Sector-specific productivity shocks in a matching model - Dennis Wesselbaum (Kiel Institute for the World Economy (IfW), 2010)
Shocks driving the business cycle have different effects on low-skilled and high-skilled workers. This paper studies the effects of temporary and permanent sector-specific shocks in a New Keynesian matching model. We show that temporary sector-specific shocks have reallaction and aggregate effects. Permanent shocks explain wedges in real wages and different performances in labor markets. Furthermore, the model is able to replicate an aggregate Beveridge curve.
More recent version: http://hdl.handle.net/10419/130547
Keywords: E24; J24; J41; 330; Beveridge Curve; Matching; Sectoral Productivity Shock